Hanging Out in International Politics: Two Kinds of Explanatory Political Ethnography for IR2. Issue 2 (26th February 2015) - MacKay, Joseph; Levin, Jamie
<x xml:space="preserve">Abstract</x> The use of ethnographic methods is on the rise in International Relations. However, research in this area has largely been constrained to critical or interpretive analysis of nontraditional objects of study. This has been driven in part by two practical problems that limit ethnographic analysis: that of aggregation, as international phenomena are necessarily large in scale, and that of access, as institutional settings are often closed or secretive. While we commend critical and nontraditional research for driving much‐needed expansion of the disciplinary agenda, we offer a complementary account, arguing that scholars can also use ethnographic methods in explanatory research. To do so, we draw on two methodological literatures in anthropology. The first approximates ethnographic research through historical immersion. The second applies ethnographic methods at multiple research sites, tracking transnational phenomena across them. The paper sketches prospective studies of each kind, concerning the creation and implementation of the United Nations. While neither method is entirely new to IR, the methodological literatures in question have yet to receive systematic treatment in the field.